Fungal dysbiosis facilitates inflammatory bowel disease by enhancing CD4+ T cell glutaminolysis - Yu, Minhao; Ding, Hui; Gong, Shuai; Luo, Yang; Lin, Haiping; Mu, Yifei; Li, Hao; Li, Xiaobo; Zhong, Ming (Frontiers in Cellular and Infection Microbiology, 2023)
The fungal microbiota is an important component of the complex multikingdom microbial community colonizing the mammalian gastrointestinal tract and has an important role in immune regulation. However, how fungi regulate inflammatory bowel disease (IBD) is poorly understood. This study found that intestinal fungi regulate immune responses in IBD. Antibiotic-mediated depletion of fungi facilitated the development of IBD. Fungi greatly enhanced oxidative phosphorylation (OXPHOS) by enhancing glutaminolysis. Mechanistically, we found that fungi could activate the dectin-1-Syk- NF-κB signaling pathway to promote the expression of key enzymes and transporters involved in glutaminolysis. In summary, our findings reveal that fungal interactions in the human gut could be a promising therapeutic target for IBD.